Analysis of Income Determinants of Start Up Coffee Shop Business in Semarang City During The Covid-19 Pandemic (Universitas Negeri Semarang, 2022)
.The researcher decided to conduct research by focusing on the analysis of the determinants of business income in a coffee shop start-up business, namely a coffee shop that is new to startup or has just been established and or is 3 years old in the city of Semarang. This study uses a purposive sampling method with the research sampling technique is Start Up Coffee Shop as many as 70 respondents based on Roscoe theory. The independent variable is derived from each of the factors that affect operating income according to production theory, supply theory and digital economic theory namely the variables of venture capital ( X1 ) , length of business ( X2) , work experience ( X3 ), working hours ( X4 ) , labor ( X5 ) , and technology ( X6 ) . While the dependent variable is operating income ( Y ). The data analysis technique used multiple regression analysis. The results showed that the variables of working capital ( X1 ) , labor ( X5 ), and technology ( X6 ) had a significant positive effect on operating income. While the variables for length of business ( X2 ) , work experience ( X3 ), working hours ( X 4 ) does not have a positive effect on the income of a coffee shop start-up in Semarang City. This is the result of research before the existence of covid 19. Meanwhile, when there was covid 19, the only variable that had a positive effect on operating income was the technology variable ( X 6 ).